Usability of serum annexin A7 as a biochemical marker of poor outcome and early neurological deterioration after acute primary intracerebral hemorrhage: A prospective cohort study - Wang, Chuan-Liu; Xu, Yan-Wen; Yan, Xin-Jiang; Zhang, Cheng-Liang (Frontiers in Neurology, 2022)
Objective Annexin A7 (ANXA7), a calcium-dependent phospholipid-binding protein, may act to aggravate brain injury. This study aimed to assess the clinical utility of serum ANXA7 as a predictor of severity, early neurological deterioration (END), and prognosis after intracerebral hemorrhage (ICH). Methods A total of 126 ICH patients and 126 healthy controls were enrolled. Symptomatic severity was evaluated utilizing the National Institutes of Health Stroke Scale (NIHSS) score. The lesion volume of ICH was measured according to the ABC/2 method. END was referred to as an increase of 4 or greater points in the NIHSS score or death at post-stroke 24 h. The unfavorable functional outcome was a combination of death and major disability at post-stroke 90 days. Results Serum ANXA7 levels were significantly higher in patients than in controls (median, 46.5 vs. 9.7 ng/ml; P < 0.001). Serum ANXA7 levels were independently correlated with NIHSS score [beta: 0.821; 95% confidence interval (CI): 0.106–1.514; variance inflation factor: 5.180; t = 2.573; P = 0.014] and hematoma volume (beta: 0.794; 95% CI: 0.418–1.173; variance inflation factor: 5.281; t = 2.781; P = 0.007). Serum ANXA7 levels were significantly elevated with increase in modified Rankin scale scores (P < 0.001). Also, serum ANXA7, which was identified as a categorical variable, independently predicted END and an unfavorable outcome with odds ratio values of 3.958 (95% CI: 1.290–12.143; P = 0.016) and 2.755 (95% CI: 1.051–7.220; P = 0.039), respectively. Moreover, serum ANXA7 levels efficiently differentiated END (area under the curve: 0.781; 95% CI: 0.698–0.849) and an unfavorable outcome (area under the curve: 0.776; 95% CI: 0.693–0.846). Conclusion Serum ANXA7 may represent a useful blood-derived biomarker for assessing the severity, END, and prognosis of ICH.